The Challenges of Developing Buguma Town as a Secondary City in Rivers State Nigeria - Charles, Victor Owitubo; Nwiekpigi, Naluba Goody (NIU Journal of Social Sciences, 2019)
This study investigated the challenges of developing Buguma as a secondary city in Rivers State. This study made use of public opinion survey research design with a sample size of 200 respondents. Data was sourced from the research instrument known as developing Buguma Secondary City Questionnaire (DBSCQ) designed along the Likert-type 4-point scale rating. Data was analyzed with both descriptive and inferential statistics. Simple percentage was used to analyze the descriptive and inferential statistics. Simple percentage was used to analyze the socio-demographic background of the respondents while mean and standard deviation were used to analyze the research questions. One way analysis of variance (ANOVA) was used to analyze the hypotheses. The results of the study revealed that majority of the respondents were male 108 (54%); were graduates 68(34%), were between 40-49 years of age 61(30.5) were civil servants 114(57%), and were mainly from the Abbey-Karibo 80(40%) administrative block. The hypothesis revealed that there is significant variation in the opinions of respondents on the challenges of developing Buguma as a secondary city. The study concludes by recommending that both the local government council and the Rivers State government should embark on massive infrastructure development to attract more people to the town to enhance its development as a secondary city to change the narrative of Rivers State as a state with one city syndrome, Port Harcourt. Keywords: Challenges, Secondary, City, Developing.